DENGUE PREVENTION PRACTICES AND ITS DETERMINANTS FACTORS IN PURWOKERTO, CENTRAL JAVA - Sahida Woro Palupi; Devi Octaviana; Siwi Pramatama Mars Wijayanti (Public Health Department, Faculty of Health Sciences, Jenderal Soedirman University, 2020)
Background Dengue Hemorrhagic Fever (DHF) is a disease transmitted through the bite of Aedes aegypti and Aedes albopictus that have been infected with the dengue virus. PSN DBD (DHF mosquito breeding areas elimination) is one of the most effective ways to prevent DHF. DHF is an endemic disease in Banyumas regency. This research aimed to analyze the factors that influence the behavior of PSN DHF in the East Purwokerto District, Banyumas Regency. Methods This research was quantitative research using a cross-sectional approach. The populations in this research were 17.289 households and the sample was housewives in East Purwokerto district taken by simple random sampling technique with 96 respondents. The data collection technique was carried out by using questionnaires and observation. Data analysis was conducted by univariate, bivariate, and multivariate.Results Education (p=0,129), income (p=0,170), knowledge (p=0,254), attitude (p=0,942), facilities availability (p=0,130), role of community figures (p=0,712) and role of health workers (p=0,635) showed has no significant correlation with behaviour of PSN DHF. Information media exposure (p=0,004) showed has significant correlation and the main factor of PSN DHF. Conclusions: Media exposure is the most influential variable in the behavior of PSN DHF. One of the advice given was to the health institution to should give more various ways of information related to dengue prevention in the community.